2020
DOI: 10.5897/jeif2019.1019
|View full text |Cite
|
Sign up to set email alerts
|

Market opening and economic growth in Nigeria

Abstract: Market opening positively impacts economic growth due to reduction in the cost of capital and international risk diversification, amongst others in Nigeria. Using a robust set of econometric approach involving unit root test, co-integration, vector error correction model and granger causality, there is evidence that current value of economic growth responds to disequilibrium from past values of real gross domestic product, stock market development, foreign direct investment, trade openness, inflation and banki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…The negative effect on the short run could also come from government policies that discourage foreign investments (say high taxes) put in place.The results showed that most SSA countries encourage FDI using direct and indirect measures and this reflect on the GDP growth as can be observe in the short and long run. The results are consistent with the correlation matrix and apriori expectation plus the findings of Ogbebor et al. (2020).…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…The negative effect on the short run could also come from government policies that discourage foreign investments (say high taxes) put in place.The results showed that most SSA countries encourage FDI using direct and indirect measures and this reflect on the GDP growth as can be observe in the short and long run. The results are consistent with the correlation matrix and apriori expectation plus the findings of Ogbebor et al. (2020).…”
Section: Methodssupporting
confidence: 91%
“…Using panel vector auto-regression model and the Granger causality test, the results revealed that bond market development, stock market development, inflation rate and real interest rate are demonstrable drivers of economic growth in the long run. Ogbebor et al. (2020) use a VECM and causality tests to study the case of Nigeria from 1986 to 2016.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dividend per share, a crucial financial metric, signifies the dividend declared for each equity share during a specific period. While investors commonly prioritize earnings per share as an indicator of a company's performance, there is a prevalent understanding that dividend declarations may not always accurately reflect the true state of a company's performance (Siyanbola & Adedeji, 2014). Khan (2012) underscored the significance of dividend per share for investors, highlighting that dividends not only act as a source of income but also offer a valuable means to evaluate a company from an investment perspective.…”
Section: Dividend Per Share and Market Price Per Sharementioning
confidence: 99%